ANALISIS STRATEGI PEMASARAN TERHADAP PEMBIAYAAN PENSIUNAN PEGAWAI NEGERI SIPIL PADA BANK SYARIAH - Anggista Marbella; Muhammad Iqbal Fasa; Is Susanto (PT. Intelek Cendikiawan Nusantara, 2024)
This article examines the marketing strategies implemented by Islamic banks in pensionfinancing products for civil servants (PNS) in Indonesia. With the increasing interest of civilservants to use Islamic financial institutions, Islamic banks face significant opportunities andintense competition in offering such products. This analysis focuses on important aspects suchas the marketing mix, segmentation, targeting, and positioning. Research shows thattransparency, adherence to sharia principles, and innovation in marketing communicationsare crucial factors in attracting and retaining customers. A more holistic and data-drivenapproach is needed to meet the needs of PNS customers who are stable and guaranteed income.The results of the study are expected to provide insights for the development of more effectivemarketing strategies, as well as improving the performance of the Islamic banking industry inIndonesia, especially in the context of pension financing. Financial education and the use ofdigital technology are also considered important to support customers in planning theirretirement. Thus, Islamic banks are expected to design products that are relevant andresponsive to market dynamics and customer needs, creating high loyalty and increasingcompetitiveness in the Islamic banking sector.